Migration Policy in the Nizhny Novgorod Region: Subjects and Management Practices - Danilova, Natalia (Vestnik Instituta sociologii, 2024)
The article examines a regional model of migration policy based on the example of the Nizhny Novgorod Region. A distinctive feature of the author's approach is the understanding of regional migration policy as a set of management practices that include both government bodies and public organisations. This approach allows us to consider migration policy as a multifaceted and complex sphere of interactions between various subjects, as well as to increase the effectiveness of the programs implemented within its framework. The main tasks in the sphere of migration policy in the region are the adaptation and integration of migrants, but there is no clear definition of these concepts and actions for their implementation. The main organisational and management structures in the region are the Migration Department of the Ministry of Internal Affairs of the Nizhny Novgorod Region, interethnic councils operating under the governor of the region and the administration of Nizhny Novgorod. Activities to include foreign citizens in regional society are not directly included in the functionality of specialised government bodies, but can be compensated by the activities of public associations. Therefore, civil society institutions, both registered associations and informal diaspora communities, should be included in management practices. In addition, unlike government bodies, they have the ability to promptly respond to requests from foreign citizens. It is noted that the identified groups of institutions participating in the implementation of migration policy have specific resources, which predetermines their functionality and the nature of their activities in management practices. Organisational and managerial institutions rely on administrative and legal resources. As the resources of civil society institutions serve communication channels among foreign citizens, high immersion and involvement in the problems of labour migrants living in the region. These circumstances require their inclusion in the development and implementation of target programs and activities of adaptation and integration orientation. The author concludes that it is advisable to create a specialised agency in the region responsible for the development and implementation of activities within the framework of regional migration policy.